Nutritional and production aspects of partially or totally replacing berseem hay by cassava in ewes feeding - Morsy A.S.; Soltan Y.A.; Saber A.M.; El-Wakeel E.A.; Ghobashy H.; Eissa M.M.; Anwer M.M.; Sallam S.M.A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
Berseem (Trifolium Alexandrinum) is the traditional winter forage in the Mediterranean-Middle East regions. In Egypt, berseem has achieved the distinction of being a base for livestock production due to its high nutritive value and easy cultivation. However, the absence of berseem during summer season cause a limiting factor for livestock production. So the objectives of this study were to evaluate the nutritional and production aspects of partially or totally replacement of berseem hay by cassava in ewes diets on ruminal fermentation, milk production and lamb performance. Forty late pregnant Barki ewes were assigned to four experimental diets (n = 10 each): i.e. control [50% berseem hay and 50% concentrate mix] or [33, 66 and 100% replacement of berseem hay by leaves and thin twigs of cassava hay] plus 50% concentrate mix for a period of 4 weeks before the expected lambing date until 8 weeks of lactation. 100% replacement of cassava resulted in increasing (p < 0.05) individual (acetate and propionate) and total volatile fatty acid concentration compared with other treatments. Ruminal NH3-N concentrations and total protozoa were decreased (p < 0.05) with 66 and 100% cassava replacement compared with control. Milk yield was improved (p < 0.05) by total replacing of cassava in addition milk fat, protein and lactose percentages were increased (p < 0.05) by 100% of cassava rather than other treatments. Lamb growth rate and weaning weight were enhanced (p = 0.022) by 100% cassava compared with other diets. Thus, using 100% replacement of berseem by cassava provides a promising source of forages for sheep with positive impacts on fermentation and ewes productivity.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)